Analysis of Factors Affecting Pregnant Women's Adherence to Iron (Fe) Tablet Intake - Erni Faturahmah; Nurul Qamarya; Efi Nurmala; Herna Wati (Sean Institute, 2024)
Background: The World Health Organization (WHO) recommends that all pregnant women receive a daily supplement containing 30–60 mg of elemental iron and 400 µg of folic acid throughout pregnancy as part of antenatal care (ANC). The 2010 Indonesian Basic Health Research (Riskesdas) reported that 80.7% of women aged 10–59 years received or purchased iron (Fe) tablets. However, 19.3% of pregnant women did not consume iron tablets, and only 18.0% consumed 90 tablets or more during pregnancy. This study aimed to analyze the factors influencing pregnant women's adherence to iron (Fe) tablet consumption. Methods: This quantitative study involved a population and sample of 28 pregnant women, selected using a total sampling technique. Data were analyzed using bivariate correlation tests with a significance level of p < 0.05. The study was conducted at Rasana'e Timur Public Health Center, Bima City, West Nusa Tenggara Province, Indonesia, in 2024. Results: The results showed that parity (p < 0.04), knowledge (p < 0.03), and motivation (p < 0.04) were significantly associated with pregnant women's adherence to iron (Fe) tablet consumption. In contrast, age (p > 0.20), education (p > 0.30), and occupation (p > 0.10) were not significantly associated with adherence to iron (Fe) tablet consumption. Conclusion: Parity, knowledge, and motivation significantly influence pregnant women's adherence to iron (Fe) tablet consumption. Therefore, health education should be strengthened to improve awareness of the importance of consuming iron supplements during pregnancy.